1999
DOI: 10.1021/es981218c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Ozone Disinfection Byproducts in Drinking Water

Abstract: Using a combination of spectral identification techniquesgas chromatography coupled with low- and high-resolution electron-impact mass spectrometry (GC/EI-MS), low- and high-resolution chemical ionization mass spectrometry (GC/CI-MS), and infrared spectroscopy (GC/IR)we identified many drinking water disinfection byproducts (DBPs) formed by ozone and combinations of ozone with chlorine and chloramine. Many of these DBPs have not been previously reported. In addition to conventional XAD resin extraction, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
166
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(169 citation statements)
references
References 25 publications
1
166
0
2
Order By: Relevance
“…First, the U.S. EPA compiled a list of DBPs to consider for prioritization. More than 600 DBPs from various disinfectant combinations that have been identified and cataloged by the U.S. EPA (20) served as an important reference. Additional DBPs were subsequently added as new information became available (21,22).…”
Section: Prioritization Approachmentioning
confidence: 99%
“…First, the U.S. EPA compiled a list of DBPs to consider for prioritization. More than 600 DBPs from various disinfectant combinations that have been identified and cataloged by the U.S. EPA (20) served as an important reference. Additional DBPs were subsequently added as new information became available (21,22).…”
Section: Prioritization Approachmentioning
confidence: 99%
“…For example, undesirable toxic oxidation by-products such as nitrosamines N-Nitrosodimethylamine (NDMA), bromate or formaldehyde can be formed Richardson, 2003;Wert et al, 2007), potentially increasing the toxicity compared to non-ozonated wastewater (Petala et al, 2006;Petala et al, 2008;Stalter et al, 2010a;Stalter et al, 2010b). These oxidation products are usually more easily biodegradable and can be partially removed during biological post-filtration Richardson et al, 1999;Stalter et al, 2010a;Stalter et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have found that the use of ozonation in the water treatment process results in a decrease in the formation of THMs and HAAs upon subsequent chlorination [7][8][9]. An increase in the ozone dosages results in a concomitant decrease in the concentrations of THMs and HAAs that formed from subsequent chlorination [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%